The Effect of Board and Ownership Structure on the Possibility of Financial Distress - Joanne Jovita Jodjana; Sherin Nathaniel; Rinaningsih Rinaningsih; Titin Pranoto (Journal of Accounting and Investment, 2021)
Research aims: This study aims to examine the effect of corporate governance, specifically relating to the ownership structure and board structure, on the possibility of financial distress.